Functional comparison of SP6 RNA polymerase and T7 RNA polymerase - Julia Gutbrod; Svenja Hehn; Antonia Bangnowski; Eleanor Fritz; Andreas Marx (PLoS ONE, 2026)
RNA-based therapeutics have emerged as a powerful class of drugs, highlighted by the rapid development and success of COVID-19 vaccines. Therapeutic RNA synthesis relies on in vitro transcription (IVT), most commonly using bacteriophage RNA polymerases (RNAP) such as T7 RNAP and SP6 RNAP. However, efficient incorporation of modified nucleotides and the reduction of double-stranded RNA (dsRNA) by-products to improve pharmacokinetic properties and reduce immunostimulatory effects remain major challenges. While T7 RNAP has been extensively engineered to expand substrate tolerance and reduce dsRNA formation, engineering efforts for SP6 RNAP remain comparatively limited, and a direct functional comparison between the two enzymes is lacking. Here, we systematically compared wild-type (wt) T7 and SP6 RNAP with respect to nucleotide analogue incorporation and dsRNA formation. We evaluated engineered variants of both polymerases for their ability to incorporate the modified nucleotides 2′‑F‑UTP and 2′‑O‑methyl‑UTP during IVT. In general, T7 RNAP displayed higher yields than SP6 RNAP for long RNA transcripts and a T7 RNAP variant demonstrated the highest acceptance of 2’‑F‑UTP. However, when using 2’‑OMe‑UTP in IVT, only a SP6 RNAP enabled synthesis of a ~ 760 nt long transcript. Moreover, the assessment of dsRNA formation with both wild-type polymerases revealed that SP6 RNAP produced substantially less dsRNA than T7 RNAP during IVT. Together, these results highlight distinct and complementary strengths of T7 and SP6 RNAP. While the SP6 RNAP FA variant showed particular promise for the synthesis of mRNA containing bulky nucleotide modifications, the reduced dsRNA formation observed for SP6 RNAP wt suggests an additional advantage for improving RNA quality.